Bicomponent Cellulose Fibrils and Minerals Afford Wicking Channels Stencil-Printed on Paper for Rapid and Reliable Fluidic Platforms - Solin, Katariina; Borghei, Maryam; Imani, Monireh; Kämäräinen, Tero; Kiri, Kaisa; Mäkelä, Tapio; Khakalo, Alexey; Orelma, Hannes; Gane, Patrick A.C.; Rojas, Orlando J. (ACS Applied Polymer Materials, 2021)
Flexible and easy-to-use microfluidic systems are suitable options for point-of-care diagnostics. Here, we investigate liquid transport in fluidic channels produced by stencil printing on flexible substrates as a reproducible and scalable option for diagnostics and paper-based sensing. Optimal printability and flow profiles were obtained by combining minerals with cellulose fibrils of two different characteristic dimensions, in the nano- and microscales, forming channels with ideal wettability. Biomolecular ligands were easily added by inkjet printing on the channels, which were tested for the simultaneous detection of glucose and proteins. Accurate determination of clinically relevant concentrations was possible from linear calibration, confirming the potential of the introduced paper-based diagnostics. The results indicate the promise of simple but reliable fluidic channels for drug and chemical analyses, chromatographic separation, and quality control.
Created from Fastlane, Scopus look-up
Keywords: fluidic channel; liquid wicking materials; multisensing assay; paper-based microfluidics; stencil printing